COMPARATIVE EFFICIENCY OF CYTOCHROME C EYE DROPS DURING EXPERIMENTAL EYE DAMAGE - D. Yu. Ivkin; P. V. Burenkov; A. S. Ivkina; V. E. Karev; E. I. Eletskaya; E. D. Semivelichenko; G. A. Plisko (Разработка и регистрация лекарственных средств)
Introduction. Cytochrome C is a metabolic drug that has an antihypoxic, trophic effect, stimulates regeneration processes, and is also used in various eye diseases.Aim. The task of the work was to determine the specific activity of cytochrome C eye drops in comparison with emoxipin.Materials and methods. As a test system, Soviet chinchilla male rabbits were used, the simulation of traumatic erosion and acid burn was carried out, followed by the use of test eye drops. In forming erosion, the method of C. Hanna, J. E. O'Brien (1960) with scraping of the corneal epithelium, an acid burn in the experiment was formed under local anesthesia (0.4% inocain) application of filter paper (in the form of a circle with a diameter of 8 mm) moistened with 3% acetic acid solution with an exposure of 5 seconds on the cornea. The effectiveness evaluation was carried out on the basis of a scale proposed by the authors, which allows histologically to take into account corneal changes during the pathological process. Descriptive statistics methods were used for all quantitative data: the average sample values (M) and standard deviations (SD) were calculated. The distribution in each data sample was analyzed using the Shapiro – Wilk criterion. Under normal distribution, analysis of variance was used followed by a posteriori analysis (Tukey criterion). If the data had an abnormal distribution, the Kruskal-Wallis test was calculated.Results and discussion. The integrity of the patterns of traumatic erosion and acid burn was histologically confirmed. The therapeutic efficacy of eye drops of emoxipin in the full dose was not sufficiently pronounced and comparable to that of cytochrome C in half the therapeutic dose. Cytochrome C in therapeutic and dual therapeutic dose effectively coped with the effects of acid burn and traumatic erosion when used in the form of eye drops for 28 days.Conclusion. Cytochrome C eye drops, used at a therapeutic dose and a dose exceeding the therapeutic dose 2 times, have a pronounced regenerative effect in traumatic erosion and acid burn of the rabbit eye cornea. The effect of Cytochrome C eye drops at half the therapeutic dose, as well as the reference drug (emoxipin) at the therapeutic dose, is not very pronounced.